Follicular dendritic cell sarcoma of axillary lymph node: A rare entity presenting with diagnostic challenge - Sandip Kumar Mohanty; Debahuti Mohapatra; Shirin Dasgupta; Pranita Mohanty; Kaushambi Chakraborty (Journal of Dr. NTR University of Health Sciences, 2018)
Follicular dendritic cell sarcoma (FDCS) originating from follicular dendritic cells is an uncommon proliferation of spindle to ovoid cells with morphological and immunophenotypic diversity. While most of the FDCSs are primary tumors of lymph nodes, at least one-third of them occur in extranodal sites. A 60-year-old male presented with right-side axillary swelling without systemic features; clinically and radiologically suspected as inflammatory lesion, but cytologically diagnosed as pleomorphic sarcoma. Microscopy revealed diagnostic challenge because of complex histomorphology and architecture which was pinpointed only after a battery of immunohistochemical (IHC) studies. Broad differential diagnosis both clinically and histomorphologically ranging from undifferentiated carcinoma, melanoma, to pleomorphic sarcoma creates diagnostic pitfall. Thus, IHC plays a major role in establishing this rare entity.